2014
DOI: 10.3109/21678421.2014.959024
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory double-blind, parallel-group, placebo-controlled study of efficacy and safety of edaravone (MCI-186) in amyotrophic lateral sclerosis patients

Abstract: nOur objective was to confirm the efficacy and safety of edaravone in amyotrophic lateral sclerosis (ALS) patients. We conducted a 36-week confirmatory study, consisting of 12-week pre-observation period followed by 24-week treatment period. Patients received placebo or edaravone i.v. infusion over 60 min for the first 14 days in cycle 1, and for 10 of the first 14 days during cycles 2 to 6. The efficacy primary endpoint was changed in the revised ALS functional rating scale (ALSFRS-R) scores during the 24-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
269
3
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(286 citation statements)
references
References 28 publications
7
269
3
7
Order By: Relevance
“…A second phase II RCT (NCT00330681)141 revealed similar results (proportion serious adverse events between arms: 23.1% placebo; 17.6% edaravone). Efficacy was not demonstrated in this small study.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…A second phase II RCT (NCT00330681)141 revealed similar results (proportion serious adverse events between arms: 23.1% placebo; 17.6% edaravone). Efficacy was not demonstrated in this small study.…”
supporting
confidence: 64%
“…A phase III RCT was done in 206 patients (Clinicaltrials.gov ID: NCT01492686). Once-daily intravenous edaravone (60 mg) showed a trend toward decreased deterioration in the ALSFRS-R scores over 24-weeks141 . The occurrence of adverse events was similar between groups.…”
mentioning
confidence: 99%
“…It is characterized by the selective and gradual degeneration of motor neurons in the brain and spinal cord, leading to death 2–3 years after disease onset. The only medications available for ALS are riluzole, increasing life expectancy by only about 3 months [9], and edaravone [10], which has recently been approved by the FDA [11]. The most common mutation identified in ALS is the dynamic (GGGGCC) n hexanucleotide repeat expansion in the C9orf72 core promotor lying upstream of the coding region, which has also been shown to cause frontotemporal dementia (FTD) [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Taken in context, these studies show that edaravone protects astrocytes, oligodendrocytes, and endothelial cells from oxidative stress damage (10,11). Furthermore, clinical studies have suggested edaravone can slow the progression of disability in patients with ALS (12)(13)(14).…”
Section: Introductionmentioning
confidence: 94%
“…Studies MCI186-16 and MCI186-19 were conducted in patients with grade 1 or grade 2 ALS severity, whereas patients in MCI186-18 had grade 3 ALS severity. Safety results for the three studies have been previously published (13)(14)(15). All three studies were conducted in compliance with the Japanese Ministerial Ordinance on Good Clinical Practice and in accordance with the ethics principles of the Declaration of Helsinki, and all patients gave written informed consent.…”
Section: Integrated Safety Analysismentioning
confidence: 99%